Quantum Information Processing Via Hamiltonian Inverse Quantum Engineering (Global Journal of Science Frontier Research, 2018)
In this paper we discuss how we can design Hamiltonians to implement quantum algorithms, in particular we focus in Deutsch and Grover algorithms. As main result of this paper, we show how Hamiltonian inverse quantum engineering method allow us to obtain feasible and time-independent Hamiltonians for implementing such algorithms. From our approach for the Deutsch algorithm, different from others techniques, we can provide an alternative approach for implementing such algorithm where no auxiliary qubit and additional resources are required. In addition, by using a single quantum evolution, the Grover algorithm can be achieved with high probability 1 - 2 , where is a very small arbitrary parameter.
Keywords: hamiltonian; quantum algorithms; deutsch; grover; inverse engineering